Responding to the health impacts of climate change in the Australian desert - Campbell, D.; Stafford Smith, M.; Davies, J.; Kuipers, P.; Wakerman, J.; McGregor, Murray (The Australian Rural Health Education Network (ARHEN), 2008)
Climate change is likely to have a significant effect on the health of those living in the 70% of Australia that is desert. The direct impacts on health, such as increased temperature, are important. But so too are the secondary impacts that will occur as a result of the impact of climate change on an uncertain and highly variable natural environment and on the interlinking social and economic systems. The consequence of these secondary impacts will appear as changes in the incidence of disease and infections, and on the psychosocial determinants of health. Responding to the impacts of climate change on health in desert Australia will involve the active participation of a variety of interest groups ranging from local to state and federal governments and a range of public and private agencies, including those not traditionally defined as within the health sector.The modes of engagement required for this process need to be innovative, and will differ among regions on different trajectories. To this end, a first classification of these trajectories is proposed.